PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA LAMBANG BILANGAN ROMAWI MELALUI STRATEGI TANDUR - Setiyadi, Desi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research and development on the Mathematics students’ worksheet (LKS) on the Cardinal Symbol through TANDUR Strategy. 1) the factual condition in SD on the use of worksheets in teaching-learning, 2) the development of the mathematics LKS on the Cardinal Symbol through TANDUR Strategy, 3) the validity of the mathematics LKS on the Cardinal Symbol through TANDUR Strategy for fourth grade in elementary school 4) the effect of mathematics worksheet on TANDUR Strategy on the students’ mathematics learning achievement on Cardinal Numbers, 5) the teachers evaluation of mathematics worksheet on the Cardinal Symbol through TANDUR Strategy for the fourth graders, 6) the students respond to mathematics LKS on the Cardinal Symbol through TANDUR Strategy in for the fourth graders in elementary school. The population used was 24 students from the fourth graders of an elementary school in UPK Kebasen. The technique for collecting data was by test and non-test, namely by pretest-posttest, and expert validation, teacher evaluation, student response questionnaire. The research was that: 1) the development of mathematics worksheet on the Cardinal Symbol through TANDUR Strategy was an alternative to solving the problems, 2) the score of validity of mathematics worksheet on the Cardinal Symbol through TANDUR Strategy from the three validators was very valid, 3) There was an effect on mathematics worksheet on the Cardinal Symbol through TANDUR Strategy toward the students’ mathematics learning audit on Cardinal Numbers, 4) Teachers evaluation of mathematics worksheet on the Cardinal Symbol through TANDUR Strategy for fourth graders was very good, and 5) The student response from mathematics worksheet on the Cardinal Symbol through TANDUR Strategy was agreed very much.